Optimization of Reservoir Potential through Floating Net Cages and Fish Farming Training - Prasetyo, Rian; Komariah, Ainur; Husein, Muhammad (LPPM of NAROTAMA UNIVERSITY, 2025)
This community service program aims to optimize the reservoir potential in Karangasem Village, Sukoharjo Regency, through floating net cages and fish farming training. Addressing the lack of technical expertise among the